Músculo esquelético, insuficiência cardíaca crônica e o papel do exercício - Yamada, Andre Katayama; Voltarelli, Vanessa Azevedo; Voltarelli, Fabricio Azevedo [UNESP] (Universidade Estadual Paulista (Unesp), Instituto de Biociências, 2009)
Patients with chronic heart failure (CHF) show metabolic, hemodynamic and skeletal muscle alterations, which decrease the life expectancy. These alterations are attributed to several factors. The focus of this review was to approach the questions related to physiological, metabolic, morphological and molecular alterations which affect the muscular system of these patients. Later, it was discussed the benefits of physical exercise to this syndrome as well as the pharmacological interventions, which are in investigation aiming the treatment of the same. Some muscle alterations are already described on the literature. For example, the more predominance of type II fibers, lower oxidative enzymatic activity, muscle atrophy and elevated concentration of cytokines that affect the muscle integrity. Thus, further studies involving cellular and molecular mechanisms of skeletal muscle in order to create strategies for prevention and treatment for patients with CHF are required

Pacientes com Insuficiência Cardíaca Crônica (ICC) apresentam alterações metabólicas, hemodinâmicas e do músculo-esquelético as quais diminuem a expectativa de vida e são atribuídas a inúmeros fatores. O foco dessa revisão foi abordar as questões relacionadas às alterações fisiológicas, metabólicas, morfológicas e moleculares que afetam o sistema muscular desses pacientes. Posteriormente, foram discutidos os benefícios do exercício físico sobre essa síndrome assim como as intervenções farmacológicas que estão em investigação para o tratamento da mesma. Algumas alterações musculares já estão bem descritas na literatura. Dentre elas se destacam a maior predominância de fibras do tipo II, menor atividade enzimática oxidativa, atrofia muscular e elevada concentrações de citocinas, as quais afetam a integridade muscular. Assim, são necessários estudos futuros que envolvam os mecanismos celulares e moleculares do músculo-esquelético com o intuito de criar estratégias de prevenção e tratamento para os pacientes com ICC.
Skeletal muscle, chronic heart failure and the role of the exercise
Keywords: Chronic Heart Failure; Skeletal Muscle; Physical Exercise; Therapy